Perancangan Sistem Pengukuran Kinerja dengan Metode Balanced Scorecard - Erly Damayanti (Jurnal Teknik Industri, 2008)
The competitive working neighborhood, company needs a plan to create the future of organization through change which was done since now. Along this time, PT Mayatama Manunggal Sentosa focused only in financial while measured the performance. But in reality, the company often got complains from customers so that there needed certain method to conclude the problem. In order to conclude the problem, there used Balanced Scorecard Method since the method translate organization’s vision, mision, and strategy in balanced way through four perspective. They were financial perspective, customer perspective, internal business process also learning and developing process. From the work performance measurement system of PT Mayatama Manunggal Santosa, there existed strategic destination, Key Performance Indicator and map strategy. Then there existed a weighed strategy through Analytical Hierrarchy Process (AHP) while the next step was relation system between perspective and strategic destination destined to map strategy. The result of work performance in third period 2007 by using OMAX method and Traffic Light System there was got 13 KPI in green indicator, 8 KPI with yellow colour and only 1 KPI in red colour, it was tempered glass production amount, so that management needs to do an exact repair to increase the performance in the next period.